RETRACTION: The Basic Concept of Narratology and Narrative - Panggabean, Devi Sari; Rangkuti, Rahmadsyah (Language Circle: Journal of Language and Literature, 2020)
A careful analysis of the paper entitled Ã¢â‚¬Å“The Basic Concept of Narratology and NarrativeÃ¢â‚¬Â (2020), authoredÃ‚Â by Devi Sari Panggabean, Rahmadsyah Rangkuti,Ã‚Â published in Volume 14, Issue 2. ofÃ‚Â Language Circle, pp.Ã‚Â 184-190 has led us to the conclusion that this contribution was essentially similar to another paper authored byÃ‚Â M. Amerian, L. Jorfi entitled Ã¢â‚¬Å“Key concepts and basic notes on narratology and narrativeÃ¢â‚¬Â (2015), which had been published in Scientific Journal of Review,Ã‚Â http://sjournals.com/index.php/SJR/article/view/1927/pdf.Ã‚Â Ã‚Â One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.